Fire Detection Design Based on Gas Leakage Accompanied by fire Location Point Using ESP32 Based on IoT - Wibowo, Nanda; Zarory, Hilman; Mursyitah, Dian; Ullah, Aulia (Program Studi Teknik Elektro Universitas Khairun, 2025)
Type B fires are fires that occur due to the burning of fuel in the form of gas, this type of fire occurs quite often where in DKI Jakarta this type of fire occurs in up to 180 cases and one of the causes of this fire is due to LPG gas leaks then at this time the fire extinguisher fire only has 1 method to find the location of the fire, therefore in this research a tool was created that can detect gas leaks and fires which can send danger warning messages to users, namely building owners and firefighters via the telegram application, from research carried out by the tool created to successfully detect the presence of gas leaks when the PPM value of LPG gas exceeds 100 PPM as well as fires when the presence of fire is detected, the carbon dioxide value in smoke exceeds 100 PPM, and also high temperatures, the tool will identify dangerous conditions and send a danger warning message to the user along with the coordinates and Google Maps link for the location of the equipment when a fire occurs.